Automotive Safety 2024 : proceedings of the 14th International Science and Technical Conference Automotive Safety (Sandomierz, Poland, 24-26 April 2024) - Jaśkiewicz, Marek; Jurecki, Rafał; Szumska, Emilia (CRC Press / Taylor & Francis Group, 2025)
Automotive Safety 2024 presents a comprehensive selection of 36 papers from the 14th International Science and Technical Conference: Automotive Safety 2024. The intricate nature of safety issues and continuous advancements in automotive technology drive a steady stream of novel and captivating scientific and technical developments at each edition of the Conference. The contributions delve into a wide range of automotive safety topics, from broad-based studies to specific applications, encompassing object recognition, accident reconstruction, autonomous vehicles, driver behaviour, micromobility, and the perception of intelligent technologies. This book constitutes significant and insightful additions to the knowledge in automotive safety, serving as a potential impetus for further scholarly endeavours